Medicalização da infância: estudo sobre as pesquisas dos programas de pós-graduação em educação e psicologia no Brasil (2010-2020) - Morais, Brunesa Paulus de (2022)
The present research is linked to the studies carried out by the Postgraduate Program in Education of the Universidade Estadual do Oeste do Paraná – UNIOESTE Research Group called Teaching Learning and Cultural-Historical Theory (GEPEATH), which is inscribed in the Research Line Culture, Educational Processes and Teacher Training. Childhood medicalization is part of a broad spectrum, i.e., life medicalization, and is inserted as a massive strategy to face the alleged difficulties in the learning process and/or conduct problems manifested by children, especially in the school context. This strategy tends to transpose heterogeneous social and daily problems to the biological and individual homogenizing dimension, blaming the subjects and exempting other social institutions from responsibility. The medicalization phenomenon has been the study's target in an attempt to demonstrate how human suffering and existence itself have been pathologized since early childhood. In this sense, the objective was to understand the discussions about the childhood medicalization process in the Brazilian graduate studies in Education and Psychology scope, at the master's level, using qualitative research inserted in knowledge state type: bibliographic, descriptive, and inventory. To this end, mapping was carried out (October 2021) through the Brazilian Digital Library of Theses and Dissertations (BDTD), delimiting the time frame of ten (10) years: from 2010 to 2020; the period that coincides with the Forum on Medicalization of Education and Society (FSMES) (2010) creation, whereas the literature suggests an increase in research after its start. As a theoretical foundation, this study starts from the Historical-Cultural Theory (THC) foundation, which has its philosophical and epistemological bases in HistoricalDialectical Materialism. The results indicate that the difficulties in the learning process and behavior problems manifested by children in the school context are not taken as dysfunctions that affect the biological body. And, as a remediator of the tensions inside the school, the medical interventions resonate in the collective imagination as being responsible for the child's biological and cognitive functioning improvement, being responsible for his/her learning and development. The use of psychotropic drugs in childhood is then justified to account for the "problem child"; the child who does not keep up with other classmates in the corresponding education stages; the child marked by suffering processes, regardless of what they are. Moreover, the capitalist society demands added to the pharmaceutical industry interests contribute to the promotion of inadvertent medicine, propagating forms of relationships based on psychotropic drugs, also affecting the training of teachers, their conceptions, and practices. This subject demonstrates relevance and a collective discussion need, so that family members, teachers, and other professionals form a unit to protect children and confront medicalization processes. Finally, the research corresponds to a movement to understand the childhood medicalization phenomenon, historically dated knowledge and contextually situated, therefore, changeable and permeated with gaps. Thus, it is suggested the extension of studies and research to theses, and congresses in the area, from journals to the school context, especially to build knowledge together. Besides, of course, listening to and welcoming the main people involved in the process: the children.